Great Power Competition and the Path to Democracy : The Case of Georgia, 1991-2020 - Burkadze, Zarina (Book collections on Project MUSE., 2022)
"Following the collapse of the Soviet Union, newly formed transitional regimes took up the challenging task of democratization. Democracy promotion in some cases produced unintended consequences. A retrospective evaluation of Georgia shows that democracy emerged even though it was the target of competition between the West and Russia. This book explores the conditions under which external pressures led to democracy and argues that competition between the great powers creates multiple power-checkers and incentivizes the emergence of policy compromises between local and external actors. Empowering more pro-democracy players allows them to serve as a countervailing force to the anti-democratic segments in society. The domestic pro-democracy forces do not hold sufficient veto powers to subvert authoritarian tendencies and contain external autocratizers. Consequently, democracy promoters should proactively support local counterparts. This point becomes more crucial as authoritarian great powers are rising as promoters of authoritarianism worldwide. Conversely, the security guarantees provided by authoritarian outsiders to their domestic allies are similarly important not to perceive political processes as a zero-sum game. The result: power is shared, and a peaceful environment is created for building democracy. Western democratizers should view autocracy promotion as a challenge and an opportunity to pursue countervailing strategies while checking local democrats and preventing them from abusing their powers. Great power competition can be productive when local elites turn the external incentives to their advantage"--